Numerical Study on the Relationship between the Dominant Frequency of Blasting Vibration and the Development of Plastic Zone in Cylindrical Charge - Da Liu; Xiaohua Zhao; Jianglin Gao; Binghan Xue; Xiaobin Wu; Songtao Hu; Fang Chen (Geofluids)
Blasting vibration is a widely studied harmful effect of rock blasting excavations. Many factors affect its dominant frequency, which makes analyzing, evaluating, and predicting it difficult. This study explored the factors influencing the dominant frequency of blasting vibrations in the case of a spherical charge. Based on symmetry, a theoretical analysis in terms of a spherical explosion source is generally sufficient to describe a cavity excited by a spherical explosion charge. The elastic cavity radius and the dominant frequency of vibration induced by the spherical blasting source are closely related. However, there is a lack of relevant research on cylindrical charges. Therefore, a calculation model for a single-hole cylindrical charge was established. There is a relationship between the corresponding dominant frequency and the range of the plastic zone. The results indicate that the dominant frequency of the blasting vibration for both cylindrical and spherical charges is closely related to the range of the plastic zone formed by the rock blasting. As the elastic cavity radius increases, both the zero-crossing and the dominant Fourier frequencies decrease, and the amplitude spectrum shifts to lower frequencies. However, increasing the cylindrical charge diameter causes more changes in the plastic zone in the direction perpendicular to the cylindrical explosive axis. Moreover, increasing the charge length causes more changes in the plastic zone along this axis. It is therefore difficult to identify a unique dimensional parameter that characterizes the range of the plastic zone formed by the blasting. Because the plastic zone around a cylindrical charge is less regular than around a spherical charge, the charge weight Q is a more favorable parameter than the elastic cavity radius a when used as the main influencing factor and in an attenuation analysis for the dominant frequency of cylindrical charge blasting.